A produção capitalista do espaço: os loteamentos, os condomínios fechados e o seu papel na formação do Bairro de Nova Parnamirim/Parnamirim-RN - Nicolau, Daniel Gustavo Batista (2008)
This work exposed desired to investigate the function of evolution of closed allotment, of market of the earth and of forms of extraction of the lace of earth, in the processes capitalist production of urban space in Nova Parnamirim, community of Parnamirim/RN. This tendentious urbanization were marked for an expressive increase of number of horizontal and vertical closed residences joint ownership concerning at social groups more privileged financial position. Go after, set off, a temporal investigation, based in the forms of appropriation of space in the middle intermediate by action of the several producers agent of capitalist capital. This way, make necessary understand the past of local structure earth, in order that to make possible analyze the beginning of the process. Not enough, appealed the publics institutions as immobile notary s office and secretary municipal for to collect the more important information, and in the field through of application of formulary together the population of ward, in order that of examine the motivation of residential establishment inside. Make this, confirmed that the actual spatial organization of ward of Nova Parnamirim started of two allotments: the Vale do Pitimbú Park and Eucaliptos Park, both divided in several little allotments. Before of begin the ward, allotments reproduced set off from that native has been consigned during the 80, 90 decade s and begin the actual century, resigning a complicated urban structure earth, dynamized by exploration of a promising residential area. Leashed of this, confirmed the installation of logic of segregation and auto-segregation conducted by an immobile market which exclude the poor class and absorb rich class, motivate by perspective of obtaining of urban lace of earth by immobile promoter. However, perceived that the growth this market was promoted by migration of groups of capital, interior of state and others regions of country. Not distant, horizontal and vertical closed residences represent production forms of a new form of residence, corresponding the pattern architectonic as socioeconomics, strengthened by ideal of security, quality of life, necessity of reclusion and of proximity of Natal. Is in the capital which this individual found possibilities of attend satisfactory minimum of yours necessity in relation a consumption of bens and specialized and specifics services. Before this qualitative perceive that the social and spacial differential of Nova Parnamirim was the responsible by soil and habitation valorization of ward, that reinforce the promotion of segregation and of auto-segregation, and consequently, of capitalist reproduction of urban space